Relationship Between Sleep Duration and Suicidal Ideation Among Farmers: Safety for Agricultural Injuries of Farmers Cohort Study of Jeju, Korea - Jung-Hwan Oh; Jeong Rae Yoo; Seo Young Ko; Jeong Ho Kang; Sung Kgun Lee; Wooseong Jeong; Gil Myeong Seong; Hyun Jung Lee; Sung Wook Song (Elsevier, 2021)
Background: This study was conducted to identify the association between sleep duration and suicidal ideation among farmers in Korea. Methods: We used Safety for Agricultural Injuries of Farmers cohort data collected from September 2015 to June 2018, which was an agricultural survey on the health and behaviors of adult farmers in Jeju island, Korea. Results: A total of 964 participants were included in the analysis, and 3.7% of them were identified with having suicidal ideation. The frequencies of average daily sleep duration of <6 h (short sleep), 6-8 h (normal sleep), and >8 h (long sleep) were 24.4%, 70%, and 5.6%, respectively. Multivariate analyses revealed that short sleep duration was significantly associated with suicidal ideation compared with normal sleep duration (odds ratio = 2.49, 95% confidence interval = 1.07-5.77). Conclusion: Our findings suggest that short sleep duration in farmers result in higher suicidal ideation. Because individuals who have suicidal ideation often commit suicide, careful monitoring is required to prevent suicide in farmers with short sleep duration.